The Effect of Differences in Fishing Time in Handline Fishing Tools on Catches in Blimbingsari Waters - Nurshandy, Martha (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Indonesian waters are waters with enormous potential. This study aims to examine the effect of differences in fishing time on hand line fishing gear on catches in Blimbingsari waters. The analysis in this study used a quantitative descriptive analysis with a purposive sampling technique in taking the sample. This research showed that 48% of the number of catches was influenced by the time of catch and 52% was influenced by other factors, while the weight of the catch was 36% affected by the time of catch and 64% was influenced by other factors. As for the difference in catching time, the morning catch produces more fish compared to the catch during the day.